« DtrP » IN 2 KINGS 25 : SOME FURTHER THOUGHTS - Begg, Christopher (Revue biblique, 1989)
This article takes as its starting point suggestions recently put forward by F. García López in RB 94 (1987), 222-232 concerning the Deuteronomistic redactional stratum designated by W. Dietrich as "DtrP" in 2 Kings 25. Proceeding from this basis, the study attempts to point up further thematic dimensions to the material in 2 Kings 25 identified by Garcia López as "DtrP" and to identify additional elements deriving from this stratum in the chapter. In this the article aims to make a modest contribution to the continuing task of reconstructing the process of formation of the Deuteronomistic History. Cet article prend comme point du départ les suggestions récentes de F. García López dans RB 94 (1987), 222-232. Celles-ci traitent de la couche deutéronomiste que W. Dietrich désigne comme « DtrP » dans 2 Rois 25. A partir de là, cette étude tâche de signaler les autres dimensions thématiques discernables dans 2 Rois 25 que Garcia López identifie avec « DtrP », et aussi d'identifier d'autres éléments qui dérivent de cette couche dans ce chapitre. Ainsi, l'article a pour but de contribuer modestement à la tâche de reconstruction du processus de formation de l'histoire deutéronomiste.